Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/lsa.2016.126
|View full text |Cite
|
Sign up to set email alerts
|

Broadband, sensitive and spectrally distinctive SnS2 nanosheet/PbS colloidal quantum dot hybrid photodetector

Abstract: Photodetectors convert photons into current or voltage outputs and are thus widely used for spectroscopy, imaging and sensing. Traditional photodetectors generally show a consistent-polarity response to incident photons within their broadband responsive spectrum. Here we introduced a new type of photodetector employing SnS2 nanosheets sensitized with PbS colloidal quantum dots (CQDs) that are not only sensitive (~105 A W−1) and broadband (300–1000 nm) but also spectrally distinctive, that is, show distinctive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 34 publications
1
75
0
Order By: Relevance
“…Figure 5c shows the normalized response versus input pulsed frequency, from which the 3 dB bandwidth of the Schottky junction device is estimated to be ≈20.1 kHz. Such 3 dB frequency is much higher than that of SnS 2 /PbS hybrid detector (≈50 Hz), [56] and PtSe 2 / CdTe (≈6.2 kHz), [57] but slightly lower than that of Sn-containing perovskite NIR photodetector (≈100 kHz). [58] Table 1 summarizes the main device parameters of the PdSe 2 /perovskite detector and other devices with similar configurations.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5c shows the normalized response versus input pulsed frequency, from which the 3 dB bandwidth of the Schottky junction device is estimated to be ≈20.1 kHz. Such 3 dB frequency is much higher than that of SnS 2 /PbS hybrid detector (≈50 Hz), [56] and PtSe 2 / CdTe (≈6.2 kHz), [57] but slightly lower than that of Sn-containing perovskite NIR photodetector (≈100 kHz). [58] Table 1 summarizes the main device parameters of the PdSe 2 /perovskite detector and other devices with similar configurations.…”
Section: Resultsmentioning
confidence: 99%
“…It has attracted increasing research interest recently owing to its promising application in safety monitoring, spatial optical communication, chemical/biological imaging, and light vision . Hitherto, tremendous efforts have been devoted to the design of wide broadband light harvesting structures through the combination of different functional materials . However, the fabrication methods are usually complicated or employing expensive instruments.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Therefore numerous attempts have been made to combine these 2D nanosheets with semiconductor nanostructures, this kind of hybrid photodetectors achieves ultrahigh responsivity due to the synergism between the strong absorption of semiconducting nanostructures and the extremely fast conduction of carriers within the 2D nanosheets. [6][7][8][9] These hybrid photodetectors, such as graphene/PbS, 6 graphene/ZnO, 7 MoS 2 /PbS, 8 SnS 2 /PbS 9 et al have already demonstrated outstanding performance. Unfortunately, all of them are on the micron scales and the fabrication must undergo extremely complex and precise processes for example, 2D nanosheets synthesized by chemical vapour deposition must transfer onto substrates, 2D nanosheets prepared by exfoliation are all on the micron scales, and photodetectors with micro-size channel length which assembled on substrates must use photolithography, all of which are unt for large-size device fabrication.…”
Section: Introductionmentioning
confidence: 99%